TRACE METAL ANALYSIS IN FRESH AND WEATHERED CRUDE OILS (Biological Sciences - PJSIR, 2022)
Energy dispersive X-ray fluorescence spectroscopy was used to determine Fe, Cd, Pb, Ni, Mn, Zn, Cu, V, As, Hgand Se in the Nigerian fresh and weathered crude oils. Weathered crudes consisted of fresh crudes weathered for 2, 7and 14 days under ambient outdoor conditions. Vanadium, nickel, iron and copper concentrations in both the fresh andweathered crudes ranged from 12 to 114 ppm; 4.2 to 12 ppm; 45 to 182 ppm and 22to 81 pprn respectively. Other metals,i.e. lead, cadmium and manganese were observed atthe 0.42 to II ppm level whereas mercury, zinc, arsenic and seleniumwere present in very low level (0 - 0.02 ppm). For the weathered report, the valueswere increasing as weatheringprogressed. An attempt was made to assess the applicability of V:Ni ratio for passive tagging of oils.